Bijdrage tot de geschiedenis der sociaal-democratie. - Mehring, Franz; Jungmann, J.A. (Arnhem : van Marle H.W., 1881)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek